PENINGKATAN PENGETAHUAN ORANG TUA TERHADAP PERSONAL HYGIENE ANAK KELOMPOK B TK NUSA INDAH MELALUI MEDIA STANDING POSTER - May Dwi Ayu Irawati; Indriana Warih Windasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to improve parents’ knowledge of early childhood personal hygiene through the development of an educational medium in the form of a standing poster at TK Nusa Indah, Sumberkare Village, Probolinggo Regency. Personal hygiene is a crucial aspect in supporting children’s health and independence; however, many preschool children still depend on their parents for basic self-care activities. This research employed a Research and Development (R&D) approach consisting of problem identification, preliminary data collection, needs analysis, product design, expert validation, revision, and limited trials. The research subjects were parents of Group B students selected using purposive sampling. Data were collected through observation, interviews, questionnaires, and documentation. Quantitative data were analyzed using pretest–posttest comparisons, while qualitative data were analyzed thematically. The findings indicated that the developed standing poster media was feasible and effective in enhancing parents’ knowledge of children’s personal hygiene. Improved parental knowledge positively influenced children’s hygiene habits and independence in daily self-care practices. Therefore, standing poster media can serve as an effective educational tool to support collaboration between families and schools in promoting health and independence among early childhood learners.